The Influence of Social Media, Search Engines, Mobile Ads and Online Display Ads on Brand Awareness of Voucher X Products - Siahaya, Aubrey; Tarigan, Samuel (Green Publisher Indonesia, 2024)
This study comprehensively examines the impact of digital marketing strategies on increasing brand awareness of product X vouchers in Indonesia. Employing a quantitative approach and regression analysis, this research reveals that social media and search engines play a highly significant role in enhancing brand visibility and recall among consumers. These findings indicate that marketing efforts focused on social media platforms and search engine optimization (SEO) have successfully reached a broader audience and fostered higher levels of engagement. Conversely, mobile advertising, despite its significant potential, has not demonstrated a significant impact in the context of this study. The results of this research offer crucial implications for marketing practitioners, highlighting the importance of allocating greater resources to marketing activities on social media and search engines, as well as reevaluating mobile advertising strategies to ensure the relevance and effectiveness of advertising messages. Overall, this study contributes valuable insights to a deeper understanding of the dynamics of digital marketing within the evolving Indonesian market.